Learning strategies and the speaking skills in fourth grade students EGB at Unidad Educativa Interamericano, school year 2019-2020 - González Zambrano, Narcisa Ninoska (2020)
English is a necessary language for all kind of people around the world. Being able to speak English to communicate is an important goal in language learning. The learning process requires strategies that can help students improve their skills, among them speaking. Even though this skill is considered important, is also the most difficult to master, especially for students of English as a second language. For this reason, it turns necessary to set appropriate strategies to improve this skill. This research work is directed to determine the importance of learning strategies in the speaking skills in Fourth grade students EGB at Unidad Educativa Interamericano, school year 2019-2020. It was observed that students showed important difficulties to communicate in English language. They were not able to produce short dialogues and were not likely to be motivated to participate in class discussions. For this reason, this study proposes the selection of appropriate learning strategies to help students improve their speaking skills…..